Essence of comprehensive dentistry scrutinized from dental care experience of advanced general dentists - Wongnavee, Kuntira; Tantipoj, Chanita; Yuma, Suraphong; Buranachad, Naiyana (Mahidol Dental Journal, 2020)
This research explores the essence of comprehensive dental care based on experience of advanced general dentists (Tacit knowledge) with the ultimate goal of directing dental care strategy. Data were collected from 20 advanced general dentists by using an in-depth interview technique. After intensive and careful process of content and thematic analyses, we could extract 4 meanings of comprehensive dental care that are kindness care, integrated care of both dental and mental health, patient-centered treatment, and multidisciplinary treatment. It is of importance for the dentist to listen to the patient with open mindedness. Treatment should be conducted as needed by the patient not by the dentist. This approach establishes good relationship between the dentist and patient, which lead to the happiness and success in dental treatment. The extracted essence can be divided into 2 main categories: knowledge in dentistry and understanding in human beings. The dentists who perform the comprehensive dental care should develop knowledge, treatment skill, and human understanding skill. It will encourage more happiness in both the dentist and the patient.